Spring start here : learn what you need and learn it well - Spilcă, Laurenţiu (Manning Publications, 2021)
Spring Start Here teaches Java developers how to build applications using Spring framework. Informative graphics, relevant examples, and author Laurenţiu Spilcă's clear and lively writing make it easy to pick up the skills you need. You'll discover how to plan, write, and test applications. And by concentrating on the most important features, this no-nonsense book gives you a firm foundation for exploring Spring's rich ecosystem.